2017
DOI: 10.4314/rj.v4i1.2b
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in enrollment and graduation rates in private and public higher learning institution in Rwanda

Abstract: This study provides a situation analysis of enrolment and graduation rates between female and male students in public and private higher learning institutions in Rwanda. The study tracked graduation rates of female and male students for nine years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…But study skills are not the only factors affecting female students' academic achievement. Tusiime et al (2017) revealed other factors affecting female students in their academic pursuit including early motherhood, loss of parents or guardians, poor performance in A level examinations, family duties, and lack of counseling services related specifically to gender and gender stereotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But study skills are not the only factors affecting female students' academic achievement. Tusiime et al (2017) revealed other factors affecting female students in their academic pursuit including early motherhood, loss of parents or guardians, poor performance in A level examinations, family duties, and lack of counseling services related specifically to gender and gender stereotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is an indication that, in Rwanda, female students are fewer in higher education than their male counterparts. As Tusiime et al (2017) argue, there is an underrepresentation of females in Rwandan public universities (31.1% of female against 68.9% of males) mainly because male students generally perform better than females at the upper secondary level which is the main factor determining admission to public universities.…”
Section: Participantsmentioning
confidence: 99%
“…While female students are in the majority in countries like Mauritius, Lesotho, Tunisia and South Africa, they are concentrated in the arts and social sciences disciplines (Teferra and Altbach, 2004;Vincent-Lancrin;, FAWE, 2010, with very low participation in STEM disciplines. This appears to be a global phenomenon, although the level of disparity differs across countries (Bunyi, 2003, FAWE, 2010UNESCO, 2012;Tusiime et al, 2017). Worldwide, female students are underrepresented in computer science and engineering (Tusiime et al, 2017;Cheryan, Master and Meltzoff, 2018).…”
Section: Enrolment Trends By Gender In Tertiary Educationmentioning
confidence: 99%
“…This appears to be a global phenomenon, although the level of disparity differs across countries (Bunyi, 2003, FAWE, 2010UNESCO, 2012;Tusiime et al, 2017). Worldwide, female students are underrepresented in computer science and engineering (Tusiime et al, 2017;Cheryan, Master and Meltzoff, 2018). This is likely to perpetuate underrepresentation in the future since girls and women lack role models.…”
Section: Enrolment Trends By Gender In Tertiary Educationmentioning
confidence: 99%
See 1 more Smart Citation